2012
DOI: 10.1111/j.1740-8709.2012.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary counselling on food habits and dietary intake of Finnish pregnant women at increased risk for gestational diabetes – a secondary analysis of a cluster‐randomized controlled trial

Abstract: The incidence of gestational diabetes mellitus (GDM) is increasing and GDM might be prevented by improving diet. Few interventions have assessed the effects of dietary counselling on dietary intake of pregnant women. This study examined the effects of dietary counselling on food habits and dietary intake of Finnish pregnant women as secondary outcomes of a trial primarily aiming at preventing GDM. A cluster-randomized controlled trial was conducted in 14 municipalities in Finland, including 399 pregnant women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 27 publications
5
27
3
Order By: Relevance
“…[28][29][30][31] However, 7 years are a long time, and several factors have affected women's lifestyle. Mothers with small children may have had lack of time and may have got tired to follow the recommended lifestyle habits which were discussed during the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30][31] However, 7 years are a long time, and several factors have affected women's lifestyle. Mothers with small children may have had lack of time and may have got tired to follow the recommended lifestyle habits which were discussed during the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Our cluster randomised controlled trial (RCT) in Finnish pregnant women at increased GDM risk showed that lifestyle counselling was effective in controlling the proportion of large-for-gestational-age new-borns and improving the women's diet, and preventing excessive gestational weight gain and decrease in physical activity. [28][29][30][31] One year after delivery, the prevalence of MeS among women with GDM risk factors was 16-18% depending on the criteria; with no differences between the intervention and usual care group. 24 Our aim is to study MeS and its components 7 years postpartum among Finnish women who in early pregnancy were at increased risk of developing GDM (intervention or usual care), among women with early pregnancy GDM diagnosis and among women without GDM risk factors during pregnancy (healthy control).…”
Section: Introductionmentioning
confidence: 97%
“…The NELLI trial showed that the lifestyle counselling was effective in controlling the proportion of large-for-gestational-age newborns and improving the women's diet and had a minor effect on gestational weight gain and decrease in physical activity [21, 3133]. Since participation in followup measurements at one year postpartum was low (24% of the original cohort) and the total number of participants was modest, the results must be interpreted carefully.…”
Section: Discussionmentioning
confidence: 99%
“…Observational evidence suggests that healthy diets before and during pregnancy may reduce the risk of GDM . Randomised controlled trials have shown improvements in diets after dietary and lifestyle counselling for pregnant women at increased risk of GDM . However, counselling initiated already before pregnancy may be more effective in preventing GDM.…”
Section: Introductionmentioning
confidence: 99%